(untitled) (International Journal of Ayurveda and Pharma Research, 2020)
Eight countries accounted for 66% of the new cases with India (27%) at top. Anti-TB drugs are one of the commonest group underlying idiosyncratic hepatotoxicity worldwide. Ayurveda is living science which is helpful to each individual to be a healthy by advocacy of lifestyle and treatment by universal principle. In present scenario the role of Ayurveda in the management of TB is very scanty and mostly limited to adjunct or supportive therapy which cannot be simply neglected. In this review an attempt is made to throw a light on history of tuberculosis, it’s related literature in Ayurveda classics, different Kalpas and drugs which may useful, and their anti-tubercular potential and current trend of practice and research on tuberculosis. The main objective is to make familiar the researchers and readers to take further initiative in future to conduct more research on this contagious killer disease.